Prognosis of cardiovascular events after implantation of a cardioverterdefibrillator in patients with chronic heart failure: the value of increasing concentration of endothelin-1 and soluble forms of ST2 protein in blood plasma - A. T. Teplyakov; N. I. Tarasov; L. K. Isakov; E. V. Grakova; M. N. Sinkova; K. V. Kopieva; О. B. Garmaeva; O. N. Ogurkova; V. V. Kalyuzhin; E. V. Kalyuzhina (Бюллетень сибирской медицины, 2018)
Aim. The purpose of this study was to examine the association of increasing concentrations of endothelin-1 and soluble forms of ST2 protein (sST2)  in the blood plasma of patients with chronic heart failure (CHF) who underwent implantation of a cardioverter-defibrillator, with the development of cardiovascular events (death from cardiovascular diseases, decompensated CHF, acute coronary syndrome or acute ischemic stroke) to determine whether these biomarkers can be used as predictors of an unfavorable course of the disease.Material and methods. A 6-month cohort study included 40 patients with CHF who received an ICD 4-12 weeks before their inclusion in the study. At the beginning of the study the concentrations of endothelin-1 and sST2 in plasma by ELISA were analyzed, along with conventional diagnostic techniques typical of a specialized cardiology clinic.Results. Phenotype with a favorable course of the disease was identified in 21 patients (group 1), and with a unfavorable course was seen in 19 (group 2). The concentration of endothelin-1 and sST2 in the blood plasma of the 2nd group patients was higher than in patients of the 1st group. The link of cardiovascular events with high levels of soluble ST2 protein and endothelin-1 in blood plasma has been identified. Variation of the decision rule threshold on the ROC-curve has allowed sST2 concentration of 34.93 ng/ml to be determined as a cutoff  point.  Accuracy of two-class classification (determination of  the posterior probability of cardiovascular events) after identifying such cut-off  point was characterized by 93%  sensitivity and 72% specificity (area under ROC-curve – 0.87).  If the value of the plasma concentrations of sST2 more 34.93 ng/ml the relative risk of cardiovascular events was 4.4 (95% CI 1.7–11.1). The use of endothelin-1 surplus in plasma (cut-off point – 0.34 fmol/ml) in predicting cardiovascular events was lower: the sensitivity – 88%, specificity – 68% (area under ROC-curve – 0.74). When the concentration of endothelin-1 in blood plasma was more than 0.34 fmol/ml the relative risk of cardiovascular events was 2.7 (95% CI 1.2–6.3).Conclusion. The increase in the sST2 and endothelin-1 concentration in blood plasma may be considered as a predictor of cardiovascular events in CHF patients after implantation of cardioverter-defibrillator.